2013
DOI: 10.5539/ibr.v6n3p140
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Rural Banks Effectiveness in Ghana

Abstract: This study critically examines contemporary issues and lending activities to small scale farmers for agricultural production. The Agriculture sector is the mainstay of Ghana's economy and small scale farmers play a dominant role in the sector which explains why this study concentrates on this sector. A survey research was conducted using both structured and unstructured questionnaires. A total of 127 farmers, 18 key informants and 10 rural banks were interviewed. Descriptive and inferential statistics were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Before their setup, Bank of Ghana (BOG) mandated that agricultural loans should represent 50% of any rural banks credit portfolio, 30% for cottage industry and finally 20% for trading. The study of Kadri et al [10] on the importance of rural banks in Ghana concluded that rural bank's credit lending operations have failed to meet the BOG requirements, hence depriving the agricultural sector of its 50% mandatory sectoral allocation. In this study, it was observed that rural banks credit portfolio comprises of agricultural (6.85%), cottage industry (8.6%), trade (39.2%) and Social loans (45.35%) This suggests that agricultural loans are given less priority by rural banks in terms of loan disbursed.…”
Section: Allocations Of Rural Bank's Credit Portfoliomentioning
confidence: 99%
See 1 more Smart Citation
“…Before their setup, Bank of Ghana (BOG) mandated that agricultural loans should represent 50% of any rural banks credit portfolio, 30% for cottage industry and finally 20% for trading. The study of Kadri et al [10] on the importance of rural banks in Ghana concluded that rural bank's credit lending operations have failed to meet the BOG requirements, hence depriving the agricultural sector of its 50% mandatory sectoral allocation. In this study, it was observed that rural banks credit portfolio comprises of agricultural (6.85%), cottage industry (8.6%), trade (39.2%) and Social loans (45.35%) This suggests that agricultural loans are given less priority by rural banks in terms of loan disbursed.…”
Section: Allocations Of Rural Bank's Credit Portfoliomentioning
confidence: 99%
“…Many publications focused on either the regional context of the country in addressing the significance of rural banks while others focused on the crop subsector at large. For instance, Kadri, and Afful et al [10,11] evaluated the importance of rural banks in Ghana and come to a conclusion that the agriculture sector was deprived of working capital as compared to the other sub-sectors of the economy. The limitation of these studies is their inability to identify an export earning crop and point out the importance of rural credit in its productivity.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Appendixes B, the most significant risk factors when evaluating SME for a loan are the difficulty with which the loan default can be evaluated and how informal the business is. In Ghana, a study by Kadri et al (2013) indicates that rural banks consider collateral security as the most important factor in granting loans to small scale farm businesses.…”
Section: Scope Of Sme Problemsmentioning
confidence: 99%
“…Studies have showed that a sustainable measure of obtaining regular supply of raw materials for industrial production is giving out financial support/assistance to farmers. 34 Ghana's agricultural sector, which is dominated by smallholder farmers, is declining due to the challenges of unfavourable rainfall patterns, limited access to credit facilities, lack of machinery and inputs, among others. As such, farming activities according to International Fund for Agricultural Development 35 thrives well with good and sound capital base/credit facilities.…”
Section: Characteristics Background and Operations Of The Jommentioning
confidence: 99%